Desire to get drunk partially mediates effects of a combined text message-based alcohol intervention for young adults. (1st May 2023) - Suffoletto, Brian; Chung, Tammy
Abstract: Background: This study aimed to test the causal effect of different text message interventions on reducing alcohol consumption indirectly by altering desire to get drunk. Methods: Participants were young adults randomized to interventions with different behavior change techniques: self-monitoring alone (TRACK); pre-drinking plan feedback (PLAN); post-drinking alcohol consumption feedback (USE); pre- and post-drinking goal feedback (GOAL); and a combination of techniques (COMBO) who completed at least 2 days of both pre- and post-drinking assessments over 12 weeks of intervention exposure. On the two days per week they planned to drank alcohol, participants were asked to report desire to get drunk (0 "none" to 8 "completely"). The next day, participants reported drinking quantity. Outcomes included binge drinking (defined as 4+ drinks for a woman and 5+ drinks for a man) and drinks per drinking day. Mediation was tested using path models of simultaneous between-person and within-person effects using maximum likelihood estimation. Results: At the between-person level, controlling for race and baseline AUDIT-C and within-person associations, 35.9 % of the effects of USE and 34.4 % of the effects of COMBO on reducing binge drinking were mediated through desire to get drunk. 60.8 % of the effects of COMBO on reducing drinks per drinking day were mediated through desire to get drunk. We did not find significant indirect effects for any other text-message intervention. Discussion: Findings support the hypothesized mediation model where desire to get drunk partially mediates the effects of a text message intervention using a combination of behavior change techniques on reducing alcohol consumption. Highlights: Desire to get drunk predicts same-day alcohol consumption in young adults. A combined text message intervention (COMBO) reduced the desire to get drunk, which in turn, reduces alcohol consumption. Other interventions using isolated behavior change techniques reduced alcohol consumption but not through desire.